Positive Attitude of Users in Mediating the Impact of Perceived Benefits and Convenience on the Interest in Using QRIS Regularly in Daily Life - Resti Prima; S. Suryadi; Osly Usman (Golden Ratio of Data in Summary, 2026)
Digital transformation in the financial sector encourages the use of payment systems rather than cash methods, such as QRIS (Quick Response Code Indonesian Standard). However, behavioral intentions to use QRIS routinely still face challenges, particularly regarding user perceptions and attitudes. This study aims to analyze the influence of perceived usefulness and perceived ease of use of QRIS (perceived ease of use) on the intention to use QRIS regularly (behavioral intention to use), with a positive attitude toward QRIS's benefits and ease (attitude toward using) as a mediating variable. A quantitative approach was used through a survey of 160 respondents who lived in one of the apartments in Tebet, South Jakarta, who were actively using QRIS. The analysis was carried out using SmartPLS software version 4.1.1.2 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. The results showed that the benefits obtained and the ease of use of QRIS had a significant effect on positive attitudes and intentions to use QRIS regularly, and that positive attitudes mediated the relationship between the two. These findings reinforce the relevance of the Technology Acceptance Model (TAM) for cashless payments in urban areas.